Effect of drought stress on the formation of yield elements in spring barley and the potential of stress expression reduction by foliar application of fertilizers and growth stimulator - I. Svobodová; P. Míša (Plant, Soil and Environment, 2004)
Spring barley plants were exposed to water stress at different growth stages - from the period after emergence to the beginning of stem elongation, from emergence to the end of anthesis and from the beginning of stem elongation to the end of anthesis in pot experiments. In variants exposed to water deficit from emergence to the end of anthesis and from the beginning of stem elongation to the end of anthesis, effects of foliar fertilizers and Atonik preparation (applied before the growth stage DC 30 or at DC 33) to lower the stress impacts were tested. During the growing season, formation and reduction of tillers, florets per spike and the yield structure at full ripeness were investigated. The water deficit at stem elongation caused a withering out of the established tillers, drought during the formation of the florets reduced their number as well as their development into grains. In the variant where water stress was present to the beginning of stem elongation, the plants were able to compensate for stress implications by productive tillers that developed later (at stem elongation). The previous water deficit did not decrease 1000-grain weight, however protein content in grain increased due to low grain yield per pot. If foliar fertilizers and Atonik were applied before DC 30, a reduction of fertile florets decreased, which led to slight increase in a grain number per spike.